Unsustainable Glacier Ablation at 78° N latitude, Linnébreen, Svalbard, 2005 - Caleb Schiff (Arctic Data Center, 2013)
Understanding the amount and timing of stream inflow to Linnevatnet is of critical importance when attempting to quantify sedimentation. Linnebreen, located 6km south of Linnevatnet, is the largest source for inflow to Linnevatnet. Mass balance measurements, via traditional stake methods, provide a tool to quantify Linnebreen’s contribution. Furthermore, mass balance studies shed light on the larger climatic regime of the area during the year of observation and provide a means to determine the “health” of the glacier. Historical records of Linnebreen’s 20th century retreat are preserved in aerial photos. Analysis of photos can give insight into the rate of retreat, providing context for the assessment of Linnebreen’s “health.” As anthropogenic climate change becomes a topic of increasing scientific discussion, especially in the arctic, monitoring such ice masses acquires further significance. This study asks the following questions: What is the current “health” of Linnebreen? How has the beginning of the 21st century compared to the past 100 years? What and when does Linnebreen melt during the summer? What is the main agent of melting?